Elements of Post-Modernism and NeoMarxism in Anthony Doerr’s All The Lights We Cannot See - Fhalgun, A.Sai; Prasad Pandey, Sanjay (International Journal of Psychosocial Rehabilitation, 2021)
All the Lights We Cannot See is a novel written by American short-story writer Anthony Doerr which discusses the life of two characters Marie-Laure and Werner Pfennig and their crossing each other in a warbased scenario. Doerr discusses the idea of morality and lack of gratitude among people through his work and tries to show that human must be grateful for what he has rather than seeking for what he doesn’t. Through this paper the researcher will get to know what is Post-Modernism and Neo Marxism and their role in the novel as elements and their working which will help understand their importance in the novel